Radiation Dose from Multidetector CT - Tack, Denis.; Tack, Denis.; Kalra, Mannudeep K.; Kalra, Mannudeep K.; Gevenois, Pierre Alain.; Gevenois, Pierre Alain. (Diagnostic Imaging, 2012)
Computed tomography (CT) is a powerful technique providing precise and confident diagnoses. Close to 65 million CT examinations are performed each year in the United States alone, an astonishing number achieved with an annual double digit growth rate over the past 30 years. The burgeoning use of CT has resulted in an exponential increase in collective radiation dose to the population. Despite investigations supporting the use of lower radiation doses, surveys highlight the lack of proper understanding of CT parameters that affect radiation dose. Dynamic advances in CT technology also make it important to explain the latest dose-saving strategies in an easy-to-comprehend manner relevant to routine clinical practice.   This book aims to review all aspects of the radiation dose from CT and to provide simple rules and tricks for radiologists and radiographers that will assist in the appropriate use of CT technique. The second edition includes a number of new chapters on the most up-to-date strategies and technologies for radiation dose reduction while updating the outstanding contents of the first edition. Vendor perspectives are included, and an online image gallery will also be available to readers.